2023
DOI: 10.9734/ajahr/2023/v10i3236
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Levels of Nitrogen on Growth and Yield of Cauliflower (Brassica oleracea var. botrytis) Varieties

Abstract: Nitrogen is the major limiting nutrient in commercial cauliflower production. The effects of six nitrogen doses (0, 70, 80, 90, 115, 130 kg N/ha) were evaluated in two cauliflower varieties (Snow Mystique and Khumal Jyapu) at the Institute of Agriculture and Animal Science, Lamjung Campus from September 2018 to January 2019. This experiment was carried out in a two factorial Completely Randomized Design with twelve treatments and five replications. FYM (25 t/ha), full dose of phosphorus (80 kg/ha) and potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Probably, the higher nitrogen availability resulted in higher chlorophyll levels, which improves the plant capacity to convert light into energy for its growth and development. This hypothesis is consistent with the reports of Katuwal et al [34] who found that cauliflower plants subjected to different nitrogen levels showed an increase in head fresh weight, leaf area, and plant height, upon the augmentation of nitrogen supply. The latter is notoriously essential for the synthesis of proteins, which have a crucial role in the organization and functioning of plant cells, including the enzyme enhancement of all metabolic processes.…”
Section: Nitrate Nitrogen Phosphorus and Potassium Concentrationssupporting
confidence: 93%
See 1 more Smart Citation
“…Probably, the higher nitrogen availability resulted in higher chlorophyll levels, which improves the plant capacity to convert light into energy for its growth and development. This hypothesis is consistent with the reports of Katuwal et al [34] who found that cauliflower plants subjected to different nitrogen levels showed an increase in head fresh weight, leaf area, and plant height, upon the augmentation of nitrogen supply. The latter is notoriously essential for the synthesis of proteins, which have a crucial role in the organization and functioning of plant cells, including the enzyme enhancement of all metabolic processes.…”
Section: Nitrate Nitrogen Phosphorus and Potassium Concentrationssupporting
confidence: 93%
“…Further confirming the pivotal role of nitrogen, Katuwal et al [34] demonstrated that the application of 130 kg ha −1 N improved yield and biometrical parameters, including stem diameter and head girth.…”
Section: Nitrate Nitrogen Phosphorus and Potassium Concentrationsmentioning
confidence: 87%
“…Under optimal growing conditions, including adequate soil nutrition, proper watering and pest control, the content of bioactive substances can be significantly increased [35][36]. The cauliflower harvesting time also plays an important role in ensuring its functional properties.…”
Section: Introductionmentioning
confidence: 99%